Study the following steps. All of the statements below are correct except for one (or more). Which one is the first fallacious step? Indicate your answer with the number of the statement you think is errorneous.

If \(x=y \ne 0 \)

\( \LARGE 1) \) \(x^2 = xy \)

\( \LARGE 2) \) \(x^{2} - y^2 = xy - y^2 \)

\( \LARGE 3) \) \((x+y)(x-y) = y(x-y) \)

\( \LARGE 4) \) \(x + y = y \)

\( \LARGE 5) \) \(x + x = x \), since \(x=y\)

\( \LARGE 6) \) \(x + x = x \)

\( \LARGE 7) \) \(2x = x \)

\( \LARGE 8) \) \(2=1\), since \(x\) is non-zero.

×

Problem Loading...

Note Loading...

Set Loading...